Recent progress of methods for cuproptosis detection - Zhang, Ligang; Deng, Ruiting; Guo, Raoqing; Jiang, Yawen; Guan, Yichen; Chen, Caiyue; Zhao, Wudi; Huang, Guobin; Liu, Lian; Du, Hongli; Tang, Dongsheng (Frontiers in Molecular Biosciences, 2024)
Varying from other identified cell death pathways, cuproptosis is a new type of regulated cell death characterized by excess Cu ions, abnormal aggregation of lipoylated proteins in TCA cycle, loss of Fe-S cluster proteins, up-regulation of HSP70, leading to proteotoxic and oxidative stress. Cuproptosis is highly concerned by scientific community and as the field of cuproptosis further develop, remarkable progress has been made in the verification and mechanism of cuproptosis, and methods used to detect cuproptosis have been continuously improved. According to the characteristic changes of cuproptosis, techniques based on cell death verification, Cu content, morphology, molecular biology of protein levels of cuproptosis-related molecules and biochemical pathways of cuproptosis-related enzyme activity and metabolites of oxidative stress, lipoic acid, TCA cycle, Fe-S cluster proteins, oxidative phosphorylation, cell respiration intensity have been subject to cuproptosis verification and research. In order to further deepen the understanding of detecting cuproptosis, the principle and application of common cuproptosis detection methods are reviewed and categorized in cellular phenomena and molecular mechanism in terms of cell death, Cu content, morphology, molecular biology, biochemical pathways with a flow chart.All the indicating results have been displayed in response to the markers of cuproptosis, their advantages and limitations are summaried, and comparison of cuproptosis and ferroptosis detection is performed in this study. Our collection of methods for cuproptosis detection will provide a great basis for cuproptosis verification and research in the future.